Hadith #27 - Sahih al-Bukhari - Sa'd Abu Mjahd al-Ta'iy سعد أبو مجاهد الطائي الكوفي (Sahih al-Bukhari)
Allah’s Messenger (ﷺ) distributed (Zakat) amongst (a group of) people while I was sitting there but Allah’s Messenger (ﷺ) left a man whom I thought the best of the lot. I asked, “O Allah’s Messenger (ﷺ)! Why have you left that person? By Allah I regard him as a faithful believer.” The Prophet (ﷺ) commented: “Or merely a Muslim.” I remained quiet for a while, but could not help repeating my question because of what I knew about him. And then asked Allah’s Messenger (ﷺ),
Grade: Sahih

Hadith #1824 - Sunan Ibn Majah - Abu Hurairah; Ali bin Muhammad bin Ishaq al-Tanafasi علي بن محمد بن إسحاق الطنافسي; Sa'd Abu Mjahd al-Ta'iy سعد أبو مجاهد الطائي الكوفي; Waki' bin al-Jarrah وكيع بن الجراح (Sunan Ibn Majah)
“When the Prophet (ﷺ) took an oath he would say: ‘By the One in Whose Hand is the soul of Muhammad.”‘
Grade: